GC-MS Based Chemical Profiling and Evaluation of Antioxidant Potential of Leaves and Stems of Alternanthera Sessilis Red from Sabah, Malaysia - Mohammad Shaheen Khan; Samina Khan Yusufzai; Lim, Yi Ying; Wan Zulnashriq (IJPPS, 2018)
Objectives: The aim of the current study was to perform phytochemical screening and determination of total phenolics, total flavonoids and antioxidant activity of various crude extracts of Alternanthera sessilis red leaves. Methods: Determination of antioxidant nature of Alternanthera sessilis red was carried out by DPPH radical scavenging method. GC-MS analysis of various crude extracts resulted in the presence of different types of low and high molecular weight compounds consisting of carbohydrates, fatty acid and vitamins. Results: Among all the extracts, methanol extracts exhibited higher DPPH radical scavenging activity with IC50 value of 0.183 mg/ml. BHT used as the positive control showed IC50value of 0.089 mg/mL. The results suggested that the crudes extracts of Alternanthera sessilis red exhibit moderate antioxidant activity. The total phenolic content (279.8 Â± 0.02 mg GAE/g) and total flavonoid content (250.7 Â± 0.03 mg QE/g) in methanol was estimated higher as compared to other solvents. Conclusion: The total flavonoid content and total phenolic content wereÂ found to be higher in methanolic extract followed by ethyl acetate Â and hexane extracts.